CONTENT AREA EFFECTIVENESS: ENGLISH VS FILIPINO MEDIUM OF INSTRUCTION - Domingo, Dahlia Romero (PEOPLE: International Journal of Social Sciences, 2016)
The rate of students who get low grades in the content areas is alarming, particularly in the subjects of Sciences and Mathematics. Among the different factors affecting level of achievements as considered by several studies, is the Language factor. The teaching of subjects in the content area in Philippine schools uses English as a Second Language (ESL), wherein a certain mastery of the English language has to preceed, to understanding more of the subject. It is of great importance for teachers to evaluate the methods and techniques used in the process of teaching their subjects in order to raise level of performances of the students. This mini research aims to see the result of an evaluation of a classroom instruction while using monolingual instruction in ESL, or L2 that is English instruction, as compared with the use of bilingual instruction, in this case Filipino (the native language in the Philippines) and English combination. It is the hope of the researcher that the information gathered from this endeavor shall provide an insight for language educators and mathematics teachers to join forces in developing students’ linguistic, verbal, and logical-mathematical intelligences.